The impact of AI-assisted technologies in scientific research and writing: opportunities and ethics disclosure - De Sanctis, Vincenzo; Taouki, Joanna; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2025)
Artificial intelligence (AI) has rapidly evolved from early theoretical concepts to advanced generative models capable of producing human-like text and supporting scientific research. The recent diffusion of large language models has accelerated the use of AI-assisted technologies in medical research and academic publishing, offering opportunities such as language editing, literature review support, protocol drafting, and data analysis. At the same time, these tools raise important concerns related to accuracy, originality, transparency, ethical responsibility, and the potential spread of misinformation. This editorial examines the role of AI-assisted technologies in scientific research and writing, with a focus on medical publishing. It reviews current international recommendations issued by organizations such as COPE, ICMJE, and WAME, highlighting shared principles that prohibit AI authorship and encourage disclosure of AI use, alongside substantial heterogeneity in journal policies and disclosure practices. The article underscores the need for clear governance, consistent reporting standards, and human oversight to ensure scientific integrity and trust as AI technologies continue to advance.